Environmental factors of two schools with different prevalence of childhood obesity in La Union County, 2015. - Medina Medina, Karla; Fernández Rojas, Xinia; Ureña Retana, Ivannia; Reyes Chaves, Jonathan (Población y Salud en Mesoamérica, 2017)
Objective: the aim of this study was to describe the environmental factors of families with schoolchildren from two public schools with different prevalence of overweight. Methods: the study was descriptive and included 241 families of schoolchildren from two schools of Canton La Union. These families were surveyed at their home. The survey included environmental and sociodemographic variables. Results: the school with the lowest percentage of overweight displayed the highest level of education and the highest income. The quantity of places reported for buying foods by both study groups was 91 and 101 respectively. This included mostly grocery stores, convenience stores, retail supermarkets and fast-food restaurants. The main reasons for choosing the place to buy food in both groups were the price and proximity to the place of residency. The number of locations for physical activity reported by the families of schoolchildren with the lowest prevalence of overweight doubled the one reported by families of schoolchildren with higher prevalence of overweight. Conclusions: The main difference in the environment is given by the availability of places for the practice of physical activity, which also coincides with the fact that the families of school children with a higher prevalence of overweight show lower schooling and lower income.